Size-specific dose estimates: Localizer or transverse abdominal computed tomography images? - Pourjabbar, Sarvenaz (Baishideng Publishing Group Inc, 2014)
AIM: To investigate effect of body dimensions obtained from localizer radiograph and transverse abdominal computed tomography (CT) images on Size Specific Dose Estimate. METHODS: This study was approved by Institutional Review Board and was compliant with Health Insurance Portability and Accountability Act. Fifty patients with abdominal CT examinations (58 ± 13 years, Male:Female 28:22) were included in this study. Anterior-posterior (AP) and lateral (Lat) diameters were measured at 5 cm intervals from the CT exam localizer radiograph (simple X-ray image acquired for planning the CT exam before starting the scan) and transverse CT images. Average of measured AP and Lat diameters, as well as maximum, minimum and mid location AP and Lat were measured on both image sets. In addition, off centering of patients from the gantry iso-center was calculated from the localizers. Conversion factors from American Association of Physicists in Medicine (AAPM) report 204 were obtained for AP, Lat, AP + Lat, and effective diameter (√ AP * Lat) to determine size specific dose estimate (SSDE) from the CT dose index volume (CTDI(vol)) recorded from the dose reports. Data were analyzed using SPSS v19. RESULTS: Total number of 5376 measurements was done. In some patients entire body circumference was not covered on either projection radiograph or transverse CT images; hence accurate measurement of AP and Lat diameters was not possible in 11% (278/2488) of locations. Forty one patients were off-centered with mean of 1.9 ± 1.8 cm (range: 0.4-7 cm). Conversion factors for attained diameters were not listed on AAPM look-up tables in 3% (80/2488) of measurements. SSDE values were significantly different compared to CTDI(vol), ranging from 32% lower to 74% greater than CTDI(vol). CONCLUSION: There is underestimation and overestimation of dose comparing SSDE values to CTDI(vol). Localizer radiographs are associated with overestimation of patient size and therefore underestimation of SSDE.